2020
DOI: 10.1016/j.xfnr.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paternal age on outcomes in assisted reproductive technology cycles: systematic review and meta-analysis

Abstract: Objective: To investigate whether paternal age exerts an independent effect on the clinical outcomes of assisted reproductive technology (ART) cycles. Evidence Review: Observational studies were identified through a systematic search of MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and National Health Service evidence. Data for women aged %39 years were extracted and analyzed. We included all studies, both autologous and donor oocyte, into separate analyses of the effect of paternal age on A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…The only other meta-analysis on this subject, published in 2020 by Morris and co-workers, concluded that male age does not affect live birth, clinical pregnancy or miscarriage rates when using donor oocytes (Morris et al, 2020). However, their meta-analysis only separated paternal age at 40 and 50 years, and not across the age groups of 30, 35 and 45 as was done here.…”
Section: Figurementioning
confidence: 64%
“…The only other meta-analysis on this subject, published in 2020 by Morris and co-workers, concluded that male age does not affect live birth, clinical pregnancy or miscarriage rates when using donor oocytes (Morris et al, 2020). However, their meta-analysis only separated paternal age at 40 and 50 years, and not across the age groups of 30, 35 and 45 as was done here.…”
Section: Figurementioning
confidence: 64%
“…Those that have suggest that APA may negatively impact gamete oxidative DNA damage (Nguyen‐Powanda & Robaire, 2020) and genetics (Brandt et al, 2019; Sharma et al, 2015), conception rates (du Fossé et al, 2020; Ford et al, 2000), maternal comorbidities such as gestational diabetes (Khandwala et al, 2018; Strøm‐Roum et al, 2013) and hypertensive disorders of pregnancy (Alio et al, 2012), perinatal outcomes such as low birth weight, low‐Apgar scores and premature birth (Alio et al, 2012; Khandwala et al, 2018), and the long‐term health of offspring, such as an increased risk of neuropsychiatric disorders (schizophrenia, autism and obsessive compulsive disorder) (Brandt et al, 2019; de Kluiver et al, 2017; Hultman et al, 2011; Sharma et al, 2015; Wu et al, 2012) and cancers (leukaemia, non‐Hodgkin's lymphoma and paediatric central nervous system tumours) (Hemminki et al, 1999; Murray et al, 2002). On the other hand, several studies failed to demonstrate an effect of paternal age on reproductive outcomes (reviewed in Morris et al, 2020). This could be explained by the fact that maternal and paternal ages are highly correlated with relatively little variability in the age difference; thus, many affected couples would have to be studied to distinguish any independent paternal age effect.…”
Section: Discussionmentioning
confidence: 99%
“…This is important considering the mean paternal age has also increased globally, from 27.4 to 30.9 years observed in America ( Khandwala et al , 2017 ; Bergh et al , 2019 ), and from 29.2 in 1980 to 32.1 over the last four decades in England and Wales (Birth Statistics, 2007). In a recent systematic review, both the livebirth and pregnancy rate were increased when the male age was ≤40 years old in autologous oocyte cycles, and the miscarriage rate more likely when the male was >40 years old ( Morris et al , 2020 ). Paternal age should therefore also be considered in the management of ARFD.…”
Section: Elective Ovarian Tissue Cryopreservationmentioning
confidence: 99%